Effect of Different Media on Rooting and Survival of Pear (Pyrus pyrifolia L.) Cuttings cv. Patharnakh - Rashmita; Misra, Sanyat; Tudu, Sushila; Shanker, Karuna (International Journal of Bio-resource and Stress Management, 2023)
The present experiment was conducted in the Department of Horticulture, Faculty of Agriculture, BAU, Kanke, Ranchi to study the effect of different media on rooting and survival of pear cuttings during the year 2014–15 under the chhotanagpur plateau region of Jharkand. It consisted of 15 treatments including control. All the treatments were replicated thrice in the experiment which was laid out in randomized block design. The media were soil (control), sand, FYM, leaf mould, vermicompost (each 100%), soil+sand, soil+FYM, soil+leaf mould, soil+vermicompost, sand+FYM, sand+leaf mould, sand+vermicompost, FYM+leaf mould, vermicompost+leaf mould and FYM+vermicompost (1:1) ratio. Basal portion of pear cuttings was dipped into 100 ppm IBA solution for 24 hours and then planted in nursery bed at a spacing of 15×10 cm2. The overall best performance was recorded in media soil+FYM (1:1) for most of the parameters. Numbers of roots cutting-1 (13.56), percentage (%) of rooted cuttings (69.70%), numbers of leaves (29.28), success percentage (92.59%) and survival percentage (78.18%). The media, soil+vermicompost (1:1) performed well for root length (21.90 cm) and shoot length (34.39 cm). Soil, when used alone as a growing medium showed the least response and provided unsatisfactory results for all the parameters.